Jane in love [large type] : a novel - Givney, Rachel (Harper Large Print, 2020)
At age twenty-eight, Jane Austen should be seeking a suitable husband, but all she wants to do is write. She is forced to take extreme measures in her quest to find true love - which lands her in the most extraordinary of circumstances. Magically, she finds herself in modern-day England, where horseless steel carriages line the streets and people wear very little clothing. She forms a new best friend in fading film star Sofia Wentworth, and a genuine love interest in Sofia's brother Fred, who has the audacity to be handsome, clever and kind-hearted. She is also delighted to discover that she is now a famous writer, a published author of six novels and beloved around the globe. But as Jane's romance with Fred blossoms, her presence in the literary world starts to waver. She must find a way to stop herself disappearing from history before it's too late. A modern-day reimagining of the life of one of the world's most celebrated writers, this wonderfully witty romantic comedy offers a new side to Jane's story, which sees her having to choose between true love in the present and her career as a writer in the past.